HLA-DQ-conferred risk for type 1 diabetes does not alter neutralizing antibody response to a widely used enterovirus vaccine, the poliovirus vaccine - Sioofy-Khojine Amir-Babak; Lehtonen Jussi P.; Nurminen Noora; Laiho Jutta E.; Toppari Jorma; Veijola Riitta; Lempainen Johanna; Ilonen Jorma; Knip Mikael; Hyöty Heikki (John Wiley and Sons Inc, 2025)
This study investigated whether children with HLA‐DQ‐conferred risk for type 1 diabetes (T1D) have an altered immune response to the widely‐used enterovirus vaccine, namely poliovirus vaccine, and whether initiation of autoimmunity to pancreatic islets modulates this response. Neutralizing antibodies induced by the inactivated poliovirus vaccine against poliovirus type 1 (Salk) were analysed as a marker of protective immunity at the age of 18 months in a prospective birth cohort. No differences were observed in antibody titers between children with and without genetic risk for T1D (odds ratio [OR] = 0.90 [0.83, 1.06], p = 0.30). In the presence of the genetic risk, no difference was observed between children with and without islet autoimmunity (OR = 1.00 [0.78, 1.28], p = 1.00). This did not change when only children with the autoimmunity before 18 months of age were included in the analyses (OR = 1.00 [0.85, 1.18], p = 1.00). No effect was observed when groups were stratified based on autoantigen specificity of the first‐appearing autoantibody (IAA or GADA). The children in each comparison group were matched for sex, calendar year and month of birth, and municipality. Accordingly, we found no indication that children who are at risk to develop islet autoimmunity would have a compromised humoral immune response which could have increased their susceptibility for enterovirus infections. In addition, the proper immune response supports the idea of testing novel enterovirus vaccines for the prevention of T1D among these individuals.